Energy, hydraulic and exergy analysis of a compound parabolic concentrator using hybrid nanofluid: An experimental study. (July 2022) - Khaledi, Omid; Saedodin, Seyfolah; Rostamian, Seyed Hadi
Abstract: The aim of this study is to investigate the thermal performance and exergy analysis of a new hyNF in a compound parabolic collector. The experiment on a compound parabolic collector using a hyNF as well as its exergy analysis has been performed for the first time and is considered as one of the novelties of the present study. In this regard, a CPC has been designed and constructed, and then experimental thermal performance tests on days with standard conditions were carried out. The ethylene glycol (EG)-Water hybrid base fluid (10–90% Vol.) with SiO2 (90%) and MWCNT (10%) hybrid nanoparticles have been utilized. The results showed that the use of hyNFs due to improving the thermal properties and the Nusselt number leads to an increase in thermal efficiency than the base fluid. In particular, the maximum increase in thermal efficiency by using the hyNFs was 14.27% compared to the base fluid. In addition, the exergy efficiency increased by the utilization of hyNFs. The maximum increment in pumping power using hyNFs was 9.72%, which indicates that the demand for pumping power is very low compared to the net production of the useful heat rate. Highlights: Thermal performance of CPC collector contains MWCNT-SiO2 /EG-Water hybrid nanofluid was investigated. The CPC collector was studied based on energy and exergy analyses. The thermal efficiency of the CPC collector was enhanced 14.27% by adding MWCNT-SiO2 to the base fluid. Average of exergy efficiency was increased by about 45% with the use of hybrid nanofluid. friction irreversibility doesn't have a main role on the total entropy generation rate.